PROTOTYPE DEVELOPMENT AND PERFORMANCE EVALUATION OF RF ENERGY HARVESTER FOR 2.4 GHZ BAND FOR RFID APPLICATION - BOON, SAMUEL HONG SIONG (2013)
Radio Frequency Identification (RFID) is an emerging technology which can be broadly classified as active or passive tags. Active tags have internal batteries while passive ones are battery-free and rely on Radio Frequency (RF) signal activation from a nearby reader. A major drawback for active tag advancement is limited operational life. One possible solution to overcome frequent battery replacement would be to extend battery lifespan by harvesting readily available Wi-Fi signals from its surrounding. Characterized as micro energy harvesting, RF energy source has typically small microwatt range of harvested power. Designed for low power RFID application, RF energy harvester known as a rectenna consisting of a receiving antenna attached to a rectifying circuit was evaluated.